Contribution of mitochondrial gene variants in diabetes and diabetic kidney disease - Li, Meng; Gong, Siqian; Han, Xueyao; Zhou, Lingli; Zhang, Simin; Ren, Qian; Cai, Xiaoling; Luo, Yingying; Liu, Wei; Zhu, Yu; Zhou, Xianghai; Li, Yufeng; et al. (Frontiers in Endocrinology, 2022)
Objectives: Mitochondrial DNA (mtDNA) plays an important role in the pathogenesis of diabetes. Variants in mtDNA have been reported in diabetes, but studies on the whole mtDNA variants were limited. Our study aims to explore the association of whole mtDNA variants with diabetes and diabetic kidney disease (DKD). Methods: The whole mitochondrial genome was screened by next-generation sequencing (NGS) in cohort 1 consisting of 50 early onset diabetes (EOD) patients with maternally inherited diabetes (MID) family history. 42 variants possibly associated with mitochondrial diseases were identified according to the filtering strategy. These variants were sequenced in cohort 2 consisting of 90 EOD patients with MID. The association between clinical phenotype and these variants was analyzed. Then, these variants were genotyped in cohort 3 consisting of 1571 T2DM patients and 496 subjects with normal glucose tolerance (NGT) to analyze the association between variants with diabetes and DKD. Results: Patients with variants in non-coding region had higher percentage of obesity and levels of FINS (62.1% vs 24.6%, P = 0.001; 80.0% vs 26.5% P < 0.001). The patients with the variants in rRNA had higher prevalence of obesity (71.4% vs 30.3%, P = 0.007), and the patients with the variants in mitochondrial complex I had higher percentage of upper tertile of FINS (64.3% vs 34.3%, P = 0.049). Among 20 homogeneous variants successfully captured, two known variants (m.A3943G, and m.A10005G) associated with other mitochondrial diseases were only in the diabetic group, but not in NGT group, which indicated its possible association with diabetes. The prevalence of DKD was significantly higher in the group with the 20 variants than those without these variants (18.7% vs 14.6%, P = 0.049) in participants with diabetes of cohort 3. Conclusion: MtDNA variants are associated with diabetes and DKD, and our findings advance our understanding of mtDNA in diabetes and DKD. It will have important implications for individual therapy of mitochondrial diabetes.